Window Ventilation Behavior for Overheating Evaluation: Residents’ Survey and Derived Ventilation Profiles (International Journal of Built Environment and Sustainability, 2021)
Studies have shown that night-time ventilation can greatly reduce indoor overheating during hot spells. Yet the relevant literature is largely silent on which specific time resolved window ventilation behavior can be applied for investigations with building performance simulations. The aim of this article is to close this gap in knowledge. Specifically, a survey was carried out in two German cities Dresden and Erfurt regarding window ventilation behavior on hot (outside temperature > 30 °C) and average summer days to determine how, when and for how long ventilation is actually implemented in residential buildings. The results show that approximately 80 % of respondents ventilate their living rooms and bedrooms mainly at night and/or in the early morning on both hot and average summer days – although the individual window ventilation behavior may vary significantly. The details provided by the respondents were processed to create characteristic window ventilation profiles in order to reflect the individual user behavior more realistically in future studies, especially for overheating evaluations by building performance simulation.
Keywords: Overheating, heat resilience, residential buildings, window ventilation behavior, questionnaire